14th WCCM-ECCOMAS Congress 2021
DOI: 10.23967/wccm-eccomas.2020.136
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Preserving Discretization in the Framework of a Discrete Model Problem for Large-Strain Thermo-Viscoelasticity

Abstract: The design of structure-preserving integrators is dealt with in the framework of a discrete model problem for large-strain thermo-viscoelasticity. The evolution equations pertaining to the model problem are cast in the framework of GENERIC. The GENERIC formalism provides an ideal foundation for the design of energy-momentum-entropy (EME) consistent time-stepping schemes. An analogous approach can be applied to the full continuum model for large-strain thermo-viscoelasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…[4,5]). Previous work has shown that the midpoint rule as implicit integrator is only partially structure-preserving in dependence of the choice of the thermodynamic variable (compare [6][7][8]). The energy, which has proven to be a suitable numerical stability criterion for isothermal elastic systems is not adequate for the assessment of a dissipative thermomechanic system's stability.…”
Section: Energy-momentum-entropy Consistent Discretizationmentioning
confidence: 99%
“…[4,5]). Previous work has shown that the midpoint rule as implicit integrator is only partially structure-preserving in dependence of the choice of the thermodynamic variable (compare [6][7][8]). The energy, which has proven to be a suitable numerical stability criterion for isothermal elastic systems is not adequate for the assessment of a dissipative thermomechanic system's stability.…”
Section: Energy-momentum-entropy Consistent Discretizationmentioning
confidence: 99%